Molecular dynamics simulation of temperature effects on the mechanical properties of Carbon polycrystalline - Maboud Hekmatifar; Davood Toghraie; Roozbeh Sabetvand; Shadi Esmaeili (Progress in Physics of Applied Materials)
The mechanical properties of carbon polycrystalline materials are crucial because they determine how the material responds to external forces, such as stress and strain, and environmental conditions.  By investigating the mechanical properties of carbon polycrystalline materials, researchers can develop insights into their strength, ductility, hardness, and other characteristics, which are vital for their practical applications in industries such as manufacturing, construction, and materials science. Molecular dynamics techniques enable the examination of various polycrystalline configurations and the assessment of their effectiveness. The present study investigates the effects of temperature on the mechanical properties of Carbon polycrystalline. The results show that the ultimate strength and Young’s modulus of the simulated polycrystal are 64.553 Gpa and 355.284 GPa, respectively. Also, the results showed that with increasing temperature to 320 K, Young’s modulus and ultimate strength of carbon polycrystalline increase to 363.185 and 69.417 GPa, respectively.  With a further increasing the temperature to 350 k, these parameters decrease to 349.909 and 63.047 GPa. The observed increase in these parameters at lower temperatures may be attributed to the increased atomic mobility of the samples resulting from the initial temperature enlargement. The simulation results are expected to help further understand the influence of temperature on the mechanical properties of carbon polycrystalline materials.